GLOBALIZATION AND NATIONAL SOVEREIGNTY DEFENSE OF ICONOCLASTIC VIEW - Sandretto, Rene (Journal of European Economy, 2018)
The paper studies activity of Trans National Companies as one of globalization manifestations and the TNC’s effect on the world trade. Key approaches to determination of interconnection between globalization and national sovereignty are analyzed. The author substantiates a new approach to creation and stages of globalisation development.